Propuesta de planificación estratégica para la empresa óptica Lafam Visión C.O. de la ciudad de Barranquilla. (2021)
Today trade is increasingly demanding and in society with the creation of companies they must have an inclination towards innovation and updating of the processes in these, which goes hand in hand with the exponential growth of human and change technological. In companies which are dedicated to finding a way to compete and survive in the market, that is why with the implementation of strategies such as strategic planning, which as a solution to the problems that arise in it in one way or another they must be competitive if they don't disappear. For the Optica Lafam company, by implementing this tool, it will be able to achieve its goals, achieving corporate and functional stability